Implications of the COVID-19 Pandemic for the Development and Update of Clinical Practice Guidelines: Viewpoint - Steeb, Theresa; Follmann, Markus; Hagen, Ralf Matthias; Berking, Carola; Heppt, Markus (Journal of Medical Internet Research, 2020)
Following the rapid spread of a new type of coronavirus (SARS-CoV-2), nearly all countries have introduced temporary restrictions affecting daily life, with "social distancing" as a key intervention for slowing the spread of the virus. Despite the pandemic, the development or actualization of medical guidelines, especially in the rapidly changing field of oncology, needs to be continued to provide up-to-date evidence- and consensus-based recommendations for shared decision making and maintaining the treatment quality for patients. In this viewpoint, we describe the potential strengths and limitations of online conferences for medical guideline development. This viewpoint will assist guideline developers in evaluating whether online conferences are an appropriate tool for their guideline conference and audience.
CRIS-Team WoS Importer:2021-01-15